Awareness of Saudi community toward multiple sclerosis in Qassim Region, Saudi Arabia - Al-Hamdan, Nourah A. (Neurosciences (Riyadh), 2021)
OBJECTIVES: To evaluate the awareness of Saudis in Qassim region, Saudi Arabia on multiple sclerosis (MS). METHODS: A cross-sectional study was conducted on 350 Saudis in Qassim, Saudi Arabia between January 2019 and June 2019 using a pre-designed questionnaire including socio-demographic data and questions evaluating knowledge about MS. RESULTS: The majority of studied participants were adult females (74%), between 20-30 year-old (45.1%) and with high education level or above (80.6%). Nearly one third of the studied group had good knowledge regarding MS (31.7%). Half of the studied group knew that central nervous system (CNS) is the system affected by MS, 52% reported that vitamin D deficiency, family history of MS, personal history of autoimmune disease, viruses, and obesity are the factors which increase the risk of developing MS. Approximately, 62.9% knew that blurred and double vision, numbness, paralysis or weakness and difficulty in concentration and memorizing are symptoms of MS. Female participants and those knowing someone having MS had a significant good knowledge level regarding MS than others. Getting knowledge from combined sources from internet or social media; family, friends or neighbors and health workers was significantly more prevalent among those with good knowledge. CONCLUSION: Most of the study participants had limited knowledge regarding MS. Planning health education programs for the public is essential.